(untitled) (Bangladesh Journal of Medical Microbiology, 2009)
Blood samples from randomly selected 100 newly admitted first year MBBS students of Sylhet MAG Osmani Medical College were tested to find the seroprevalence of antibodies against Hepatitis A, Hepatitis B, Hepatitis C and Hepatitis E viruses. The study revealed a lower seroprevalence of HAV antibodies than the common perception of their age group. The rate of vaccination against hepatitis B virus was found not very high, considering the affluence of their parents. Also there were lack of awareness about risk factors of viral hepatitis and many of the students were in habit of taking food outside. Institutionalized vaccination policy for 1st year medical students against Hepatitis A and Hepatitis B along with awareness building measures regarding the professional risk among the new entrants are suggested. Policy planners and other stakeholders in the field should come up with a comprehensive intervention strategy to protect the future caregivers from the scourge of hepatitis viruses. Keywords: Hepatitis A, Hepatitis B, Hepatitis C, Hepatitis E, Seroprevalence doi: 10.3329/bjmm.v3i1.2967 Bangladesh J Med Microbiol 2009; 03 (01): 20-26